2019
DOI: 10.1536/ihj.18-550
|View full text |Cite
|
Sign up to set email alerts
|

Successful Peritoneal Dialysis for the Treatment of Inotrope-Dependent End-Stage Heart Failure

Abstract: Extra-and/or intracorporeal renal replacement therapy can improve the cardiorenal hemodynamics in patients with advanced heart failure (HF) refractory to medical therapy and renal failure. Here, we report the case of a 51-year-old woman with inotrope-dependent end-stage HF and chronic renal failure due to anthracyclineinduced cardiomyopathy, in whom the induction of hemodiafiltration and subsequent chronic peritoneal dialysis (PD) provided a dramatic improvement of her cardiac hemodynamics from restrictive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The improvement in quality of life can be dramatic. PD therapy can improve the functional status of patients with severe diuretic-resistant heart failure whose vital functions can only be maintained by vasopressors [ 43 ]. Several reports have reported decreased hospitalization with PD treatment in such patients [ 44 , 45 ].…”
Section: Peritoneal Dialysis In Diuretic-resistant Heart Failurementioning
confidence: 99%
“…The improvement in quality of life can be dramatic. PD therapy can improve the functional status of patients with severe diuretic-resistant heart failure whose vital functions can only be maintained by vasopressors [ 43 ]. Several reports have reported decreased hospitalization with PD treatment in such patients [ 44 , 45 ].…”
Section: Peritoneal Dialysis In Diuretic-resistant Heart Failurementioning
confidence: 99%
“…The first reported case of treating a congestive HF patient with PD dates back to 1949 [37], but its use has gained progressive interest over the last two decades. Case reports, case series, and small cohort studies have reported favorable outcomes in different patient settings, from severely reduced to preserved ejection fraction and in various types of cardiomyopathies [10,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. PD constitutes a home-based therapeutic modality that offers the possibility of continuous and gentle removal of excess water and solutes with minimal hemodynamic impact, allows easing the renal venous and intraabdominal pressure while draining ascites and interstitial edema, and has a high capacity of customization to the patient's clinical requirements and daily life.…”
Section: The Role Of Peritoneal Dialysismentioning
confidence: 99%
“…End-stage renal disease (ESRD) has been demonstrated to be accompanied by various cardiovascular complications, which usually have poor outcomes (Kim and Parekh, 2015;Ramesh et al, 2016;Samanta et al, 2019). It has been reported that cardiovascular events, including heart failure, are the leading causes of death in ESRD patients (Kooman and van der Sande, 2019;Sugiura et al, 2019;Yogasundaram et al, 2019). The progressively deteriorating structure and function of the heart may be the consequence of renal failure (Cutshall et al, 2018;Unlu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%